Estimation of ulna length as a predictor of height in Nepalese female adult population: An anthropometric study - Sah, Rajendra Prasad; Bhaskar, Ravi Kumar (Janaki Medical College Journal of Medical Science, 2018)
Background and Objectives: Stature estimation has a valuable importance for the anatomist, anthropologist and the forensic experts. Long bones are usually used for the estimation of individual height for the said purpose since 1952. The purpose of this study is to formulate a linear regression equation for the estimation of the stature of living female adult population from the length of ulna. Materials and Methods: This research was conducted at M.B. Kedia Dental College Birgunj on 150 subjects who were chosen from among the patients and their attendants in the OPD. The height was measured from the crown to the heel and the length of the ulna was measured from the tip of the olecranon process to the tip of the styloid process. The recorded data was calculated by the standard statistical software. Results: The correlation coefficient (r) was found to be 0.55(p<0.001) for the left ulna with stature and it was 0.463 (p<0.001) for the right ulna with stature after analyzing the data. Supportive regression equations and scatter-plot diagrams could successfully interpret the height from the ulnar length of the population. Conclusion: The ulna length can be used for estimating the height of an individual. The regression equation which were proposed in this study will be useful for forensic esperts, clinicians, anatomists, archeologists, and anthropologists . Such evidence provides the investigator to gauge that aspect of an individual’s physical description.